Lenalidomide long-term neurotoxicity: Clinical and neurophysiologic prospective study. (13th September 2016) - Dalla Torre, Chiara; Zambello, Renato; Cacciavillani, Mario; Campagnolo, Marta; Berno, Tamara; Salvalaggio, Alessandro; De March, Elena; Barilà, Gregorio; Lico, Albano; Lucchetta, Marta; Ermani, Mario; Briani, Chiara
Abstract : Objective: To evaluate long-term lenalidomide neurotoxicity and correlation with cumulative dose and hematologic response. Methods: Nineteen myeloma patients (7 men, mean age 63.2 years) underwent clinical and neurophysiologic assessment at baseline and at 2 (8 patients, group A) or 5 years (11 patients, group B) after starting lenalidomide therapy for relapsed/refractory multiple myeloma. Neuropathy was scored with Total Neuropathy Score clinical version (TNSc). Lenalidomide cumulative dose was correlated with severity of neuropathy and hematologic response. Results: At enrollment, 7/19 patients (3 in group A, 4 in group B) had neurophysiologic signs of neuropathy secondary to previous chemotherapy, in 2 of them subclinical. Neurophysiologic evidence of sensory axonal neuropathy occurred in 4/8 patients at 2 years follow-up (group A) and in 3/11 patients at 5 years follow-up (group B). Dorsal sural nerve sensory action potential amplitude was the earliest neurophysiologic abnormality. No relevant (≥4) clinical changes were found in TNSc score. Hematologic overall response was 62% in group A and 100% in group B. No correlation was found between lenalidomide cumulative dose and neuropathy or between neuropathy and hematologic response. Conclusions: In our study, up to 50% of myeloma patients on long-term lenalidomide therapy developed sensory axonal neuropathy. Reduced dorsal sural nerve sensory action potential amplitude was the first neurophysiologic alteration. Neuropathy was usually subclinical or mild, however. Neurotoxicity was independent of lenalidomide cumulative dose and hematologic response.